Annual Cycle of Bacterial Secondary Production in Five Aquatic Habitats of the Okefenokee Swamp Ecosystem - Murray, Robert E. (1985)
Rates of bacterial secondary production by free-living bacterioplankton in the Okefenokee Swamp are high and comparable to reported values for a wide variety of marine and freshwater ecosystems. Bacterial production in the water column of five aquatic habitats of the Okefenokee Swamp was substantial despite the acidic (pH 3.7), low-nutrient, peat-accumulating character of the environment. Incorporation of [(3)H]thymidine into cold-trichloroacetic acid-insoluble material ranged from 0.03 to 2.93 nmol liter(−1) day(−1)) and corresponded to rates of bacterial secondary production of 3.4 to 342.2 μg of carbon liter(−1) day(−1) (mean, 87.8 μg of carbon liter(−1) day(−1)). Bacterial production was strongly seasonal and appeared to be coupled to annual changes in temperature and primary production. Bacterial doubling times ranged from 5 h to 15 days and were fastest during the warm months of the year, when the biomass of aquatic macrophytes was high, and slowest during the winter, when the plant biomass was reduced. The high rates of bacterial turnover in Okefenokee waters suggest that bacterial growth is an important mechanism in the transformation of dissolved organic carbon into the nutrient-rich bacterial biomass which is utilized by microconsumers.